A cell-free plant extract for accurate pre-tRNA processing, splicing and modification. - Stange, N (1987)
An intron-containing tobacco tRNA(Tyr) precursor synthesized in a HeLa cell nuclear extract has been used to develop a cell-free processing and splicing system from wheat germ. Removal of 5' and 3' flanking sequences, accurate excision of the intervening sequence, ligation of the resulting tRNA halves, addition of the 3'-terminal CCA sequence and modification of seven nucleosides were achieved in appropriate wheat germ S23 and S100 extracts. The maturation of pre-tRNA(Tyr) in these extracts resembles the pathway observed in vivo for tRNA biosynthesis in Xenopus oocytes and yeast in that processing of the flanks precedes intron excision. Most of the modified nucleosides (m2(2) G, psi 35, psi 55, m7G and m1A) are introduced into the intron-containing pre-tRNA with mature ends, whereas two others (m1G and psi 39) are only found in the mature tRNA(Tyr). Processing and splicing proceed very efficiently in the wheat germ extracts, leading to complete maturation of 5' and 3' ends followed by about 65% conversion to mature tRNA(Tyr) under our standard conditions. The activity of the wheat germ endonuclease is stimulated 3-fold by the non-ionic detergent Triton X-100. All previous attempts to demonstrate the presence of a splicing endonuclease in wheat germ had failed (Gegenheimer et al., 1983). Hence, this is the first cell-free plant extract which supports pre-tRNA processing and splicing in vitro.